DESAIN PROTOTYPE PENYIRAMAN PERKEBUNAN BERBASIS ANDROID - Devit Satria (Jaringan Sistem Informasi Robotik-JSR, 2019)
Most farmers still use a manual system for watering their gardens, where farmers have to collect water in the settlements when the watering time arrives and often miss the right time when farmers often are not in the garden. This research makes a system that can control plantation watering by Android. This system aims to facilitate the activities of farmers who still use physical power to water plants, the use of software in this application is Thunkable to make applications from watering plantations and hardware in the form of Arduino 1.6.9 as the system program provider on the plant watering tool, this system uses the GSM Module (Global System For Mobile) to send SMS when the farmer is not in the garden with the machine format on to turn on the water pump machine and the engine format is off to turn off the water pump engine, Bluetooth HC-06 module for short-range watering with the command in 'on' format to turn on the water pump engine and format 'off' to turn off the water pump engine with both modules sending Arduino uno instructions to turn on the relay so that the water pump engine can turn on and can water plantations. The benefit of this tool is that it can ease the burden of the activities of farmers in watering plantations remotely or at close range in order to turn on the water pumping machine.